Hukuman Pelaku Penodaan Agama Menurut al-Sunnah Dalam Perspektif Hak Asasi Manusia - Tasrif, Muh. (KALAM, 2017)
This paper discusses human right and the law of In the Reform Era, the existence of the Republic of Indonesia Presidential Decree No. 1/1965 About Prevention against Blasphemy came into a public debate. Many observers and human rights activists saw that the law is not compatible with the principles of freedom of religion guaranteed by the Constitution of 1945 and human rights. On the contrary, many leaders of Islamic organizations saw that the Law is in accordance with respect for religious freedom. Based on this context, it is interesting to raise questions of how to understand blasphemy in Islam in the perspective of human rights and its implications upon the Law in Indonesia. To answer the questions, I attempt to explain the terms used in conceptualizing actions of blasphemy. The explanation is followed by looking at forms of action of the Prophet Muhammad against perpetrators of blasphemy and interpreting it with the perspective of human rights and its implications upon the law in Indonesia. In this article, it is argued that measures of ignorance, rejection, abuse, and insult against the religion of Islam did not cause the Prophet punish the actors. The Prophet punished the actors based on that the actions had prevented Muslims from practicing their religion.In the perspective of human rights, to express a particular interpretation of religion and to seek support for the interpretation become part of freedom of religion and belief and also part of freedom of speech. For this reason, to put forward an interpretation of any religion can not be punished.